The Impact of Watching Foreign Movies Using English Subtitles on ESP Vocabulary Comprehension and Composition of Words in English - Siregar, Nelia Fariani; Wibowo, Sandi Nasrudin; Noah, Bren (Tauladan Fathimah Azzahra, 2023)
English is one of the few international languages, therefore almost all countries have English lessons. Using English language movies to develop their vocabulary comprehension is the main goal of the study as English language movies possess the benefit of authentic input. Motivating students and more opportunities to develop their vocabulary and their comprehension also the composition of words in English. This research was conducted so that we can find out the benefits we get if we use English subtitles when watching foreign series or movies. This is one way to increase the amount of vocabulary that can be mastered and make it easier for us to memorize English vocabulary. With existing subtitles, we can also understand the conversation by itself. This research will be assisted by collecting information in the form of online questionnaires through Google Forms. The conclusion obtained from this study is that by watching English films we can develop our English skills in the aspect of Listening. Second, English subtitles can have a positive impact, especially if we are trained in aspects of Reading and Writing, because by paying attention to subtitles we can understand the composition - the order of words that exist. Third, it can facilitate the enrichment of our vocabulary or vocabulary so that we have more vocabulary that we know.